Practice and Development of Agricultural Seed Management Technology in the Hilly Areas of Eastern Nepal - Wagle, Shyam Prasad (CHINTAN-DHARA, 2023)
The use of new technologies in agricultural sector is the contemporary global concern issue. This study attempts to explore about the practice and development of seed management technology in the eastern hilly areas of Nepal including the analysis of major reasons and accociated problems. Moreover, it also seeks the perception of farmers towards this technology. In addition, the study applied household questionnaire survey, key informant survey and focus group discussion with local farmers in to collect relevant information. The household survey conducted in 20 percent (190hss) in total (601hhs) of the study area ranging from 250 to 1500 masl along the Koshi-highway.The relevant published and unpublished documents: previous research journals, books, dissertations and official records were also reviewed as secondary sources of information for this paper. This paper has showed that the technology is well known for the protection and promotion of both crops and vegetables farming in the study area. More than 78 percent (150hhs) farmers are using this as a useful and profitable technique. Despite various problems, the practice of this technology is gradually increasing in this area and the maximum practice is concentrated with vegetable farming. Although it was introduced through the inspiration of local research centers at first time, the role of neighbours, friends and television programs seems to be significant respectively in its development and expansion in the study area. This technology is the choice of the farmers and the majority of the farmers are in fovor of the development and expansion of the technology.